2010
DOI: 10.1002/polb.22025
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics and crystalline morphology of poly(ε‐caprolactone) in blends with grafted rubber particles

Abstract: The crystallization behavior of pure PCL and PCL in blends with crosslinked rubber particles was studied under (non)isothermal crystallization conditions, where the rubber particles were grafted with PCL chains via hydrogen abstraction of the aliphatic moieties in PCL. The crystal growth and the organization of crystals into spherulitic superstructures are significantly influenced by the presence of the grafted rubber particles, which act as an excellent nucleating agent for PCL.The nucleating efficiency shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
4
6
0
Order By: Relevance
“…Reducing the grafting density is reducing the nucleation efficiency further. This result is in line with the result of L’Abee et al [24], who showed that in a rubber particle-filled PCL based system, the nucleation efficiency depended on grafting density. For the PCL80 matrix the behaviour is different.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Reducing the grafting density is reducing the nucleation efficiency further. This result is in line with the result of L’Abee et al [24], who showed that in a rubber particle-filled PCL based system, the nucleation efficiency depended on grafting density. For the PCL80 matrix the behaviour is different.…”
Section: Resultssupporting
confidence: 92%
“…The effect was larger in samples with a higher grafting density and shorter grafts as compared to samples with a low grafting density and longer grafts. L’Abee et al [24] showed that, during the in situ preparation of rubber particle-filled PCL, the peroxide used to cross-link the rubber network also caused grafting of PCL chains onto the rubber particles. Transmission electron microscopy (TEM) images of the grafted particles revealed lamellae growing from the surface of the particles, while also an increase in nucleation efficiency was observed which was shown to depend on grafting density [24].…”
Section: Introductionmentioning
confidence: 99%
“…The Avrami exponent n of the neat PCL shows the value 2.7 suggesting a three‐dimensional growth, in compliance with other authors . The n values evaluated from the high‐ and low‐temperature exotherms (a and b in Table ) of the nanocomposites are around 2 indicating possible change in the growth mechanism from the three‐ to two‐dimensional.…”
Section: Resultssupporting
confidence: 87%
“…In order to control crystallinity, an understanding of crystallization kinetics is important. The kinetics of crystallization of PCL and some of its blends [10,11,12,13] have been studied previously using differential scanning calorimetry (DSC), employing samples with masses of a few milligrams. However, during the processing of polymers, they are cooled at high rates and their crystallization occurs at a high supercooling.…”
Section: Introductionmentioning
confidence: 99%